Razão instrumental e preconceito: reflexões sobre o bullying - Antunes, Deborah Christina (Universidade Federal de São Carlos, 2008)
This paperwork Idiscusses Ithe Iconcept Iof Ibullying, Icharacterized Ias Ia Ikind Iof school violence that occurs in students relationship. A theoretical analysis is made in the first part of this paper. Starting at the critical of instrumental reason and the concept I of I prejudice, I both I based I on I the ICritical ITheoryI of I Society, I the I criticalI of formal and descriptive bullying is brought about. An empirical research is presented in the second part, which objective is to analyze the proximity between what is described by bullying and what is considered, here, prejudice in both empirical data collected by individual interviews and also by a discussion group with students from 8º grade of a private fundamental school. It is considered that, although both refer to similar facts and share individual and cultural determinants, they are opposed concepts. The first one collaborates to the maintenance of the status quo, while the second one recognizes on the knowledge the objective of human emancipation.
Keywords: Educação; Preconceito; Violência escolar; Teoria crítica; Razão instrumental; Bullying; CIENCIAS HUMANAS::EDUCACAO